Comparative Assessment of Toxic Metals Bioaccumulation and the Mechanisms of Chromium (Cr) Tolerance and Uptake in Calotropis procera - Usman, Kamal; Al Jabri, Hareb; Abu-Dieyeh, Mohammed H.; Alsafran, Mohammed H. S. A. (Frontiers in Plant Science, 2020)
Progressive pollution due to toxic metals significantly undermines global environmental sustainability efforts. Chromium (Cr) is one of the most dangerous to human health. The use of plants to rid the environment of such pollutants “phytoremediation” proves to be a promising alternative to the current remediation methods. In the present study, inductively coupled plasma optical emission spectroscopy (ICP-OES) determined Cadmium (Cd), Chromium (Cr), Copper (Cu), Nickel (Ni), and Lead (Pb) concentrations in the soil, and plants (Atriplex leucoclada, Calotropis procera, Salsola imbricata, Typha augustifolia, and Phragmites australis) root and shoots. Results showed that compared to other studied metals, Cr concentration was the highest in the soil at 111.8 mg/kg, whereas Cd records the least concentration of 0.04 mg/kg. Cr also accumulated in higher concentration in C. procera than in the soil and other plants, with up to 188.2 mg/kg and 68.2 mg/kg concentration in the root and shoot, respectively. In order to understand the mechanism of Cr tolerance and uptake in C. procera, germinated seeds were irrigated with 20 mg/kg Cr and control treatment (no Cr applied) for six (6) weeks under greenhouse conditions. Fourier transformed infrared spectroscopy (FTIR) results showed high Cr complexation and binding to C. procera tissues via hydroxyl and carboxylic groups. Enzymatic assay reveals increased activities of superoxide dismutase (SOD), catalase (CAT), and glutathione reductase (GR) in Cr treated C. procera than in the control. SOD activity increased by up to six (6) folds. Therefore, we conclude that C. procera is suitable for the phytoremediation of Cr polluted arid soil. Additionally, regulation of cellular homeostasis via redox signaling is essential to the Cr tolerance and detoxification mechanism.